Makna Teologi Istirahat Dan Perkembanganya Dalam Kitab-Kitab Kanonik - Samgar Setia Budhi (Sekolah Tinggi Teologi Injili Indonesia (STTII) Yogyakarta, 2021)
Theology of Rest emerged when scholars became interested in research on the sabbath. This is because the understanding of Jews, Christians and some Christian factions have different views on the meaning of the Sabbath. Although the debate over the legality of the Sabbath has reached a point where it depends on the meaning believed by each of these groups, it is necessary to conduct research on the basic meaning of the Sabbath and its development in canonical books. Thus, the theology of rest is built not only on a cultural basis, but on the revelation of God's Word. Topical analysis and intertextual texts will shed light on the basic meaning and development of the idea of the Sabbath in building a theology of rest. Finally, a theological formulation of the rest (sabbath) is based on careful analysis of biblical texts.